UPAYA PEMULIHAN PARIWISATA PASCA PANDEMI COVID-19 DI PANTAI KARANG NAWING DESA PAGELARAN KECAMATAN MALINGPING KABUPATEN LEBAK PROVINSI BANTEN - Suflani Suflani; Muhammad Zhikri Faiqurohman; Rona Aulia Berliyana; Siti Khodijah (Yayasan Education and Social Center, 2022)
The tourism sector is a contributor to state revenue in the form of foreign exchange and plays a role in increasing productivity and reducing unemployment. The Covid-19 pandemic has caused the tourism sector to be paralyzed and die so that it cannot contribute to the economy. Pagelaran Village, Malingping District is one of the villages that has beach tourism affected by Covid-19. Karang Nawing Beach, which is usually crowded with tourists, has become deserted, this has led to a decrease in the income of the local community. The method used in devotion consists of three stages. First, the preparatory phase includes preliminary observations. The second step is the stage of implementing the program in the form of a discussion. The third step is the evaluation step. This service activity can be called tourism branding, which is an option as an effort to restore the post-pandemic tourism sector in Pagelaran Village, Malingping District. Tourism branding can be done by utilizing existing social media such as Instagram, Tiktok, Youtube, and Facebook. Social media is expected to be able to reach local and foreign tourists, by disseminating information about existing tourism so that the wheels of the local community's economy come to life. In line with the purpose of the activity, currently there have begun to arrive local tourists who want to travel at Karang Nawing Beach, Pagelaran Village, Malingping District, Kabuaten Lebak